Behavior of the human immunodeficiency virus/AIDS in the Cienfuegos province (2014-2019) - Leticia Castro Morejón; Hilda María Delgado Acosta; Diana Rosa Rodríguez Delgado; Delfin Rodríguez Buergo; Roxana Gutiérrez Morán; Lisset María Martínez González (Medisur)
Background: Human immunodeficiency virus infection/AIDS continues to be a health problem despite the reduction in its incidence rates. Objective: to describe the behavior of the human immunodeficiency virus/AIDS in the Cienfuegos province from 2014 to 2019. Methods: a descriptive study was carried out, 556 patients were studied and diagnosed with the Human Immunodeficiency Virus. Chronological series of cases were used and the variables incidence, prevalence, age, sex, accessibility to antiretroviral treatment and mother-to-child transmission were analyzed. Rates and percentages were also calculated. Results: patients from 25 to 49 years of age predominated, who represented 67%. A downward trend was observed in the incidence rates of the disease in the province. At the end of 2019, 98.2% of patients were under antiretroviral treatment. No mother-to-child transmission was reported in the study period. Conclusion: The study carried out evidenced the characteristics of the human immunodeficiency virus/AIDS epidemic in the Cienfuegos province during the study period, which showed a tendency to reduce its incidence rates, as well as guaranteed access to antiretroviral treatment, which, together with care protocols, has made it possible to eliminate mother-to-child transmission.